PENGEMBANGAN SUMBER DAYA MANUSIA, KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP LOYALITAS DAN KINERJA DOSEN - -, Limgiani - (Magister Manajemen Universitas Wisnuwardhana, 2015)
Abstract This study aims to describe the human resources development, organizational commitment, job motivation, loyalty performance lecturer, analyzing the influence of the human resources development, organizational commitment, and motivation work towards loyalty and performance lecturer, analyzing the influence of loyalty towards the performance of lecturers, and analyze the influence of the human resources development, organizational commitment and motivation of working through loyalty to the performance of a lecturer. Analytical techniques descriptive analyses that used and SEM analysis. Based on the results of the analysis showed that the human resources development, organizational commitment, motivation and loyalty effect on work performance of a lecturer. Loyalty is an intervening variable that could mediate the human resources development, organizational commitment and motivation on performance lecturer, meaning that professors who are committed and have a high work motivation and supported by human resources development good will create loyalty lecturer at institutions that will ultimately improve the performance of lecturers. Keywords Human Resource Development, Job Motivation, Lecturer Performance, Loyalty, Organizational Commitment